2015
DOI: 10.1080/01411594.2015.1007373
|View full text |Cite
|
Sign up to set email alerts
|

A review of the slow relaxation processes in the glass–rubber transition region of amorphous polymers

Abstract: This article is a review that introduces several articles about slow relaxation processes, also known as slower segmental dynamics. According to the literature, the coupling effect and free volume holes are two important elements for slower micro-dynamics. In addition, the slower processes of many-body systems (blend and diluted systems) are summarised. A good numerical method for detecting multiple modes in the glassÀrubber transition region is introduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 92 publications
1
5
0
Order By: Relevance
“…The spherical Fe 3 O 4 particles helped lamellar‐like graphene to disperse into the rubber matrix because spherical particles could decrease the resistance during dispersing graphene in rubber sheets. However, in the other studies, Fe 3 O 4 particles have been found having no apparent influence on the dynamics of rubber in case of low dispersion; that also explained why Fe 3 O 4 particles had been less reported in modifying rubbers and other polymers. When applied in polar polymer materials, the dispersion of Fe 3 O 4 particles would be worse .…”
Section: Introductionmentioning
confidence: 75%
“…The spherical Fe 3 O 4 particles helped lamellar‐like graphene to disperse into the rubber matrix because spherical particles could decrease the resistance during dispersing graphene in rubber sheets. However, in the other studies, Fe 3 O 4 particles have been found having no apparent influence on the dynamics of rubber in case of low dispersion; that also explained why Fe 3 O 4 particles had been less reported in modifying rubbers and other polymers. When applied in polar polymer materials, the dispersion of Fe 3 O 4 particles would be worse .…”
Section: Introductionmentioning
confidence: 75%
“…In addition, the area of tan δ peak showed that the area of NBR/GO–PPD was decreased compared to that of NBR ( Figure 9 b). Based on the above result, we could make a conclusion that GO–PPD hybrid particles have a positive interaction with the rubber matrix [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 98%
“…The glass transition temperature (Tg) determined from the tan δ peak for all NBR/LDH composites was approximately 2 °C higher than that of the unmodified NBR, as shown in Figure 9 b, which is explained by the restriction of the mobility of NBR chains by LDHs [ 27 , 53 , 54 , 55 , 56 , 57 , 58 ]. Moreover, the Tg of NBR/LDH–SAS (5 phr) was higher than that of NBR/LDH–NO 3 (5 phr), due to the organic ingredient (SAS) in LDH–SAS increasing the interactions between LDH–SAS and the NBR matrix.…”
Section: Resultsmentioning
confidence: 99%